Penerapan Artificial Intelligence dalam Aplikasi Chatbot sebagai Media Informasi dan Pembelajaran mengenai Kebudayaan Bangsa - Santoso, Pandu Dewonoto Laut; Riski, Indah; Kholik, Nur; Akbar, Muchamad Raffi; Saifudin, Aries; Yulianti, Yulianti (Jurnal Informatika Universitas Pamulang, 2021)
The nation's culture can be said to be a very meaningful thing because with the existence of culture, a nation has its own specialties and characteristics which can differenciate itself from others, therefore, traditions can be identified as a nation's identity from a particular nation. The awareness of indonesian people towards indonesian culture, in this generation especially the younger ones is decreasing because of the fast growing globalisation era, a lot of young Indonesians are more intrigued in foreign countries culture in comparisonÂ  to their own nation's culture, this causes might involved inÂ multiple factors such as limited facilities to educate students about the uniqueness of indonesian culture. Based on these factors, the application of Artificial Intelligence technology in a chatbot application which is intended as a learning infrastructure about national culture is felt to increase the enthusiasm of the young generation and make it easier for them to get information and learn various things about Indonesian culture. Learning about national culture through chatbot applications with AI technology will certainly be more attractive than the application of conventional learning methods, the aspect of flexibility in terms of learning activities will of course also increase along with the use of chatbot applications, because a chatbot can be used anytime and anywhere without requiring any special skills or requirements in its use.